THE ROLE OF RESOURCE SHARING ON CONFLICT MITIGATION IN AFRICA - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Historically, literature pertaining to conflict management has been dominated by a debate emanating from competing methods of political power sharing. More recently, however, scholars have also begun to consider military, territorial, and economic power sharing arrangements as well as institutional alternatives to power sharing—power dividing and partition. The former alternative to power sharing was proposed by Roeder & Rothchild (2005) and has received limited scholarly attention. The latter alternative has roused a considerable degree more attention but has not been empirically analyzed with any consistent results.